miRNA expression profiling of mycosis fungoides - van Kester, Marloes S. (Mol Oncol, 2011)
MicroRNAs (miRNAs) are small RNA species that regulate gene expression post‐transcriptionally and are aberrantly expressed in many malignancies including lymphoma. However, the role of miRNAs in the pathogenesis of T‐cell lymphoid malignancies is poorly understood. Previously we examined the miRNA profile of Sézary syndrome (Sz), a leukemia of skin‐homing memory T cells. In this study we determined the complete miRNome of mycosis fungoides (MF), the most common type of cutaneous T cell lymphoma. The miRNA profile of skin biopsies from 19 patients with tumor stage MF and 12 patients with benign inflammatory dermatoses (eczema and lichen planus) were compared by microarray analysis. We identified 49 miRNAs that are differentially expressed in tumor stage MF compared to benign inflammatory dermatoses using ANOVA analysis (P < 0.05, Benjamini–Hochberg corrected). The majority of the differentially expressed miRNAs (30/49) were up‐regulated in tumor stage MF. The most significant differentially expressed were miR‐155 and miR‐92a (both up‐regulated in tumor stage MF), while miR‐93 showed the highest up‐regulation in tumor stage MF with a fold difference of 5.8. Differential expression of a selection of these miRNAs was validated by miRNA‐Q‐PCR on additional test groups (tumors and controls). None of the miRNAs up‐regulated in tumor stage MF was previously shown to be up‐regulated in Sz, and only 2 of the 19 miRNAs down‐regulated in tumor stage MF were also down‐regulated in Sz. Taken together this report is the first describing the miRNA signature of tumor stage MF.